-4 (2x+9) + 3x = 6 - 4 (x-3)
Simplifying
-4(2x + 9) + 3x = 6 + -4(x + -3)
Reorder the terms:
-4(9 + 2x) + 3x = 6 + -4(x + -3)
(9 * -4 + 2x * -4) + 3x = 6 + -4(x + -3)
(-36 + -8x) + 3x = 6 + -4(x + -3)
Combine like terms: -8x + 3x = -5x
-36 + -5x = 6 + -4(x + -3)
Reorder the terms:
-36 + -5x = 6 + -4(-3 + x)
-36 + -5x = 6 + (-3 * -4 + x * -4)
-36 + -5x = 6 + (12 + -4x)
Combine like terms: 6 + 12 = 18
-36 + -5x = 18 + -4x
Solving
-36 + -5x = 18 + -4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '4x' to each side of the equation.
-36 + -5x + 4x = 18 + -4x + 4x
Combine like terms: -5x + 4x = -1x
-36 + -1x = 18 + -4x + 4x
Combine like terms: -4x + 4x = 0
-36 + -1x = 18 + 0
-36 + -1x = 18
Add '36' to each side of the equation.
-36 + 36 + -1x = 18 + 36
Combine like terms: -36 + 36 = 0
0 + -1x = 18 + 36
-1x = 18 + 36
Combine like terms: 18 + 36 = 54
-1x = 54
Divide each side by '-1'.
x = -54
Simplifying
x = -54